Radiation hardness of PantherPix hybrid pixel detector. (7th December 2021) - Dudas, D.; Kafka, V.; Marcisovsky, M.; Neue, G.; Marcisovska, M.; Prusa, P.; Koniarova, I.; Semmler, M.
Abstract: Hybrid pixel detectors (HPD) are nowadays well known and widely used in fundamental research, e.g. in high energy physics experiments. Over the last decade, segmented semiconductor detectors have also found use in medicine. The total doses received by medical radiation detectors often reach a significant level (up to several hundreds of kGy per decade), especially in applications such as transmission portal in-vivo dosimetry. Such doses might affect detector properties. Therefore, it is necessary to evaluate their performance after absorbing a significant radiation dose. PantherPix is a novel 2D hybrid pixel detector which is designed specifically for use in radiation therapy. As was concluded in earlier studies, it is suitable for radiotherapy quality assurance (QA) and portal dosimetry. In this paper, the PantherPix radiation hardness is investigated using a 60 Co source. The dependence on dose of the full depletion voltage, leakage current, detector power consumption and detector response are provided. The PantherPix radiation tolerance has been shown to be adequate for common cumulative doses delivered to radiation detectors in radiotherapy over several decades and its performance has been verified for doses up to 3000 kGy.